2018
DOI: 10.4193/rhin17.254
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein transit test time as a tool to assess lacrimal pump function after diode laser transcanalicular dacryocystorhinostomy and external dacryocysto-rhinostomy

Abstract: FTT in the DCR-T Group was significantly lower than in the EXT-DCR Group. No other variables exhibited a statistically significant correlation with FTT. Lacrimal drainage was found to be better after T-DCR than after EXT-DCR, results which show that this procedure could prevent lacrimal pump damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[ 12 , 15 ] The prospective studies had a low risk of bias in four studies and a moderate risk of bias in five studies. [ 13 , 14 , 16 - 22 ] A risk of bias assessment is presented in Fig. 2 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 , 15 ] The prospective studies had a low risk of bias in four studies and a moderate risk of bias in five studies. [ 13 , 14 , 16 - 22 ] A risk of bias assessment is presented in Fig. 2 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This meta-analysis has included 11 studies to study the success rates, out of which only 1 study by Fiejo et al . [ 16 ] (2018)does not mention the surgical procedure in detail; the rest of all studies performed bi-canalicular intubation. Thus, it can be presumed that bi-canalicular intubation is a standard practice among many DCR surgeons worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The MT-DCR, proposed by Feijó et al, involves excising nasal mucosa with a blade scalpel instead of a laser, thus preventing mucosal thermal injury, reducing nasal fibrosis, and enhancing results, as indicated by its high efficacy rates (12,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Six patients had both endoscopic Jones I test and syringing positives and experienced postoperative epiphora, which can be demonstrated by a PPV of 88% (gap of 12%). Feijo et al 25,26 published an article demonstrating that the fluorescein transit test is more reliable to predict functional success than endoscopic Jones I test, showing a PPV of 97.4%. In their study, the dye transit time test ≤60 seconds indicated functional success.…”
Section: Discussionmentioning
confidence: 99%